2016
DOI: 10.2527/msasas2016-049
|View full text |Cite
|
Sign up to set email alerts
|

049 Physiological and molecular mechanisms associated with performance, immunometabolic status, and liver function in transition dairy cows fed rumen-protected methionine or choline

Abstract: The onset of lactation in dairy cows is characterized by high output of methylated compounds in milk when sources of methyl group are in short supply. Methionine (MET) and choline (CHOL) are key methyl donors and their availability during this time may be limiting for milk production, hepatic lipid metabolism, and immune function. Supplementing rumenprotected MET and CHOL may improve overall performance and health of transition cows. observed in response to CHOL supplementation, expression of (BHMT) and MTR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 103 publications
(173 reference statements)
0
3
0
1
Order By: Relevance
“…Methionine supplementation affected serum immune levels, with a significant increase in the serum IgG level in the HMet group and an increase in the IgM level ( Table 2 ). Previous studies demonstrated that lymphocytes have a higher requirement for methionine, because in lymphocytes precursors such as choline and homocysteine are not met by methionine regeneration through the methionine cycle [ 34 , 35 ]. Wang Han et al also demonstrated that methionine supplementation increased the plasma IgG level in dairy cows [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methionine supplementation affected serum immune levels, with a significant increase in the serum IgG level in the HMet group and an increase in the IgM level ( Table 2 ). Previous studies demonstrated that lymphocytes have a higher requirement for methionine, because in lymphocytes precursors such as choline and homocysteine are not met by methionine regeneration through the methionine cycle [ 34 , 35 ]. Wang Han et al also demonstrated that methionine supplementation increased the plasma IgG level in dairy cows [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cows fed typical dry period diets without RPM, concentrations of plasma Met and the nonessential amino acids (NEAA) Asp, Gln, Glu, Cys, Tyr, and Orn as well as glucose decrease continuously from −25 d relative to calving and remain lower in early lactation [26]. Furthermore, when compared to the 3rd week pre-partum, in the 4th week post-partum, skeletal muscle concentrations of essential amino acids (EAA), Gln/Glu, Asp/Asn, Tyr, and Ser were decreased to ∼86% [26]; thus, besides helping cows achieve optimal rates of DMI [6,14,27,28], supplementing Met, first-limiting AA for dairy cows, during the transition period could help prevent drastic decreases in muscle Met. Biologically, the supply of Met in skeletal muscle could play a key role in the initiation of translation, i.e., synthesis of Met-tRNA for binding to the initiation codon AUG [29] especially during a time when the cow still is experiencing a state of negative nutrient balance.…”
Section: Amino Acid Transportmentioning
confidence: 99%
“…Statistical p-values for the main effect of time are reported in the figures in the Supplemental File (Figures S1-S7). of essential amino acids (EAA), Gln/Glu, Asp/Asn, Tyr, and Ser were decreased to ∼86% [26]; thus, besides helping cows achieve optimal rates of DMI [6,14,27,28], supplementing Met, first-limiting AA for dairy cows, during the transition period could help prevent drastic decreases in muscle Met. Biologically, the supply of Met in skeletal muscle could play a key role in the initiation of translation, i.e., synthesis of Met-tRNA for binding to the initiation codon AUG [29] especially during a time when the cow still is experiencing a state of negative nutrient balance.…”
Section: Amino Acid Transportmentioning
confidence: 99%
“…的合成, 来对动物的免疫状态进行调控 [32] . 对小鼠细 胞蛋氨酸利用的研究发现, 淋巴细胞不能利用高半胱 氨酸和胆碱这些前体物质合成蛋氨酸, 意味着淋巴细 胞在蛋氨酸循环转甲基后不能通过再甲基化途径生成 蛋氨酸对已消耗的蛋氨酸进行补充 [54] ; 同样, 对转基因 奶牛分别饲喂瘤胃保护的蛋氨酸和胆碱, 饲喂蛋氨酸 的奶牛显示更好的免疫代谢状态 [55] ; 因此, 维护机体免 疫系统稳态的蛋氨酸需要量需高于维持生长需要量.…”
Section: 蛋氨酸通过促进免疫器官的生长发育、免疫细胞 的增殖以及参与免疫分子(细胞因子、抗体、补体等)unclassified